DEVELOPMENT OF RARA STORYTELLING APPLICATION-BASED INTERACTIVE LEARNING MEDIA TO TRAIN STORY-LISTENING SKILLS - Wulandari, Wisla; Yuliana, Rina; Tisnasari, Sundawati (JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
AbstractListening ability in elementary school is still relatively low. This is due to several factors, such as the use of attractive learning media is still rare, so the development of interactive learning media is needed. This development aims to produce interactive learning media based on the Rara Storytelling application and to determine the feasibility and response of students regarding the developed media. The research method used is research and development (R&D) using the Borg and Gall model modified by Sugiyono from stages one to six. The subjects were 31 students of 4th grade B at SDN Banjar Agung 1. The results of this research indicate that interactive learning media based on the Rara Storytelling application are “very feasible" to be used in 4th grade elementary school learning. This is proved by the validation results of media at 91.2% in the “very feasible” category, the validation results of linguists at 87.5% in the “very feasible” category, and the validation results of material experts at 83.17% in the “very feasible” category. While the analysis of student responses shows a percentage of 88.36%, this shows in the “Very Good” criteria. The results of this research indicate that the developed media is feasible and attractive to be used as an application-based learning media to train listening skills in elementary schools.Keywords: Learning Media; Application-based; Storytelling